Mediation of the Physical Activity and Healthy Nutrition Behaviors of Preschool Children by Maternal Cognition in China - Xianglong Xu (International Journal of Environmental Research and Public Health, 2016)
(1) Objective: We aimed to explore the role of social cognitive theory (SCT) of mothers in the physical activity and healthy nutrition behaviors of preschool children; (2) Methods: We used a self-administered five-point Likert common physical activity and nutrition behaviors scale in Chinese based on a social cognitive theory scale in English with established validity and reliability in the USA. The current study adopted the proportional sampling method to survey mothers of preschool children in four areas—namely, Chongqing, Chengdu, Taiyuan, and Shijiazhuang—of China; (3) Results: We included 1208 mothers (80.0% mothers of normal weight children, age 31.87 ± 4.19 years). Positive correlations were found between maternal social cognition and preschool children’s physical activity (PA) behavior (p < 0.0001). However, an insignificant correlation is observed between preschool children’s fruits and vegetables (FV) behavior, screen time (ST) behavior, and maternal social cognition; (4) Conclusions: This study provides some implications for increasing fruit and vegetable consumption, increasing physical activity time, and reducing screen time in preschool children using SCT in China. Maternal social cognition is associated with preschool children’s PA behavior, and the results suggest that maternal social cognition may not affect children FV and ST behaviors. Further research is necessary to test the mediation of maternal social cognition on preschool children’s ST behavior and the correlations between maternal social cognition and children’s ST behavior.